The impact of digital transformation on sustainability: a case of the Iranian telecom industry - Jamal Aghayari; Changiz Valmohammadi; Mahmood Alborzi (International Journal of Research in Industrial Engineering)
The corporate landscape is highly affected by two market factors, namely digitalization and sustainability. These two driving forces have been the topic of several studies on how they change management methods, businesses, and society in general. However, the point that these two trends meet each other has been mostly neglected by research studies. Modern organizations and corporations are dealing with the adopting digital transformation issue as a new strategic paradigm. The present study attempts to elaborate on the relationship between digital transformation and sustainability. Therefore, through an in-depth review of the relevant literature, critical factors and their indicators were determined, and based on the proposed conceptual model, six hypotheses were developed. Then, a questionnaire was designed and distributed among 120 Iranian experts, managers, and consultants, and 97 complete questionnaires were returned. Reliability, Content Validity Ratio (CVR), and Content Validity Index (CVI) of the questionnaire were calculated, and the hypotheses were tested through Structural Equation Modeling (SEM) using SmartPLS Software. The results showed that digital transformation significantly affected an organization's sustainability aspects through operation, customer, business model, technology, workforce, and collaboration. Digital transformation and sustainability should constitute integral parts of organizational strategy. Considering that business practices affect the environment, society, and economy, digital transformation can influence the business sustainability. Digital technologies transform markets and create novel paradigms in the industry. In addition, they present new solutions to organizations to cope with sustainability issues. Due to this importance for organizations as consumers and other stakeholders, they are sensitive to the effects of business on brand value, revenues, and company valuation.